Differential roles of NaV1.2 and NaV1.6 in neocortical pyramidal cell excitability - Joshua D Garcia; Chenyu Wang; Ryan PD Alexander; Emmie Banks; Timothy Fenton; Jean-Marc DeKeyser; Tatiana V Abramova; Alfred L George Jr; Roy Ben-Shalom; David H Hackos; Kevin J Bender (eLife)
Mature neocortical pyramidal cells functionally express two sodium channel (NaV) isoforms: NaV1.2 and NaV1.6. These isoforms are differentially localized to pyramidal cell compartments, and as such are thought to contribute to different aspects of neuronal excitability. But determining their precise roles in pyramidal cell excitability has been hampered by a lack of tools that allow for selective, acute block of each isoform individually. Here, we leveraged aryl sulfonamide-based molecule (ASC) inhibitors of NaV channels that exhibit state-dependent block of both NaV1.2 and NaV1.6, along with knock-in mice with changes in NaV1.2 or NaV1.6 structure that prevents ASC binding. This allowed for acute, potent, and reversible block of individual isoforms that permitted dissection of the unique contributions of NaV1.2 and NaV1.6 in pyramidal cell excitability. Remarkably, block of each isoform had contrasting—and in some situations, opposing—effects on neuronal action potential output, with NaV1.6 block decreasing and NaV1.2 block increasing output. Thus, NaV isoforms have unique roles in regulating different aspects of pyramidal cell excitability, and our work may help guide the development of therapeutics designed to temper hyperexcitability through selective NaV isoform blockade.